Phase transition and energy transfer of lead-free Cs2SnCl6 perovskite nanocrystals by controlling the precursors and doping manganese ions. Issue 4 (2nd October 2019) - Lin, Tsai-Wei; Su, Chaochin; Lin, Chun Che
Abstract : Perovskite quantum dots (QDs), such as all-inorganic CsPbX3 (X = Cl, Br, and I), are novel fluorescent semiconductor nanocrystals (NCs) that have attracted tremendous attention due to their excellent optical properties and great applications (e.g. display backlights, light-emitting diodes, and photodetectors). The instability and toxicity of lead-based perovskite QDs, however, are intrinsic defects that obstruct their application and commercialization. Poison is released from the lead of the unstable CsPbX3 NCs, which are generally ascribed to the labile surface, ionic character, and metastable structure. In this work, lead-free Cs2 SnCl6 perovskite NCs are successfully synthesized via hot injection. Particularly, by controlling the different precursor ratios, phase transition (CsCl to Cs2 SnCl6 ) was clearly observed from X-ray diffraction (XRD) measurements. The Cs2 SnCl6 NCs exhibited a highly efficient deep-blue emission at 425 nm, with a 55 nm Stokes shift and an 84 nm full width at half maximum (FWHM). After doping Mn ions, the preferred formation of CsSnCl3 :Mn 2+ with double-wavelength emission was demonstrated based on the XRD and photoluminescence spectra. The study showed that doping synthesis should be widely used in lead-free perovskite NCs as an important strategy for next-generation solid-state lighting.